Failure mechanisms of gentle granular soil slopes - Loke, Wai Lay. (2008)
This thesis presents an experimental study on the instability behaviour of granular soil and its implications in the interpretation of the failure mechanisms of gentle granular soil slopes. A granular fill retrieved from a reclamation site in Singapore was used in the experiments. The study was carried out by conducting specialised triaxial tests on very loose to dense specimens prepared using either the water sedimentation (WS) or the moist tamping (MT) method.